Determinan Akuntabilitas Pengelolaan Dana Desa di Kecamatan Balongpanggang Kabupaten Gresik - Vanny Lellyta Indah Novita Sriwulandari; Siti Sundari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The accountability of village fund management plays an important role in developing a village. The purpose of this study was to test and prove the effect of village apparatus competence, internal control system, information technology utilization, and community participation on the accountability of village fund management in Balongpanggang District, Gresik Regency. This research was conducted in Balongpanggang District, Gresik Regency, totaling 25 villages. The sample was taken using purposive sampling technique and obtained as many as 150 respondents who had criteria, including village officials who knew about the accountability of village fund management consisting of the village head, village secretary, finance head, planning head, Kasi Kesra, and the Village Consultative Body (BPD). Data collection techniques using primary data sourced from questionnaires. The analysis technique used was SEM-PLS. The results showed that the competence of village officials, technology utilization, and community participation had an effect on the accountability of village fund management in Balongpanggang District, Gresik Regency, while the internal control system had no effect on the accountability of village fund management in Balongpanggang District, Gresik Regency. Keywords: Community Participation, Internal Control System, Utilization of Information Technology, Village Apparatus Competence, Village Fund Management Accountability.